Simultaneous editing of two DMR6 genes in grapevine results in reduced susceptibility to downy mildew - Giacomelli, Lisa; Zeilmaker, Tieme; Giovannini, Oscar; Salvagnin, Umberto; Masuero, Domenico; Franceschi, Pietro; Vrhovsek, Urska; Scintilla, Simone; Rouppe van der Voort, Jeroen; Moser, Claudio (Frontiers in Plant Science, 2023)
The reduction of pesticides' treatments is of paramount importance for the sustainability of viticulture, and it can be achieved by a combination of strategies including the cultivation of vines (Vitis vinifera) resistant or tolerant to diseases such as downy mildew (DM). In many crops, the knock-out of Downy Mildew Resistant 6 (DMR6) proved successful in controlling DM-resistance, but the effect of mutations in DMR6 genes in not yet known in grapevine. Today, gene editing serves crop improvement with small and specific mutations while maintaining the genetic background of commercially important clones. Moreover, recent technological advances allowed to produce non-transgenic grapevine clones by regeneration of protoplasts edited with the CRISPR/Cas9 ribonucleoprotein. This approach may revolutionize the production of new grapevine varieties and clones, but it requires knowledge on the targets, and on the impact of editing on plant phenotype and fitness in different cultivars. In this work we generated single and double knock-out mutants by editing DMR6 susceptibility (S) genes using CRISPR/Cas9, and showed that only the combined mutations in VviDMR6-1 and VviDMR6-2 are effective in reducing susceptibility to DM in two table-grape cultivars by increasing the levels of endogenous salicylic acid. Therefore, editing both genes may be necessary for effective DM control in real-world agricultural settings, which could potentially lead to unwanted phenotypes. Additional research, including trials conducted in experimental vineyards, is required to gain a deeper understanding of DMR6-based resistance.